Ang2 immunoexpression vs vascular profile in chorio-villous germinative status in early-term compromised pregnancies - Ecaterina Carpenco; Veaceslav Fulga; Lilian Saptefrati; Lilia Sinitina; Valeriu David (The Moldovan Medical Journal, 2023)
Background: The angiopoietin/TIE system is one of the signalling pathways that regulate vascular development and remodelling during morphogenesis of the placental complex. Deregulation of the vascularization process is associated with primary placental insufficiency through destabilization of the maternal-fetal functional system. Disruption of expression of pro-angiogenic factors is associated with reduction of the microcirculatory bed and installation of circulatory dysfunction. The aim: Evaluation of Ang2 immunoexpression in early term compromised uterine pregnancies in the context of chorio-villous circulatory dysfunction in primary placental insufficiency. Material and methods: Abortion product from 67 patients with early term compromised pregnancies (stagnant pregnancies – 43 cases, early miscarriages – 11 cases, control batch that included 13 cases of pregnancies solved on social indications) were immunohistochemically evaluated with the marker for anti-Ang2 and anti-CD31. Results: The majority of sites analyzed were Ang2 negative, with the exception of syncytiotrophoblast, that reached the highest score (+3) in most cases. A maximum placental vascularisation index was achieved in the control group. The stagnant pregnacies batch has registered the lowest vascular density mean. Conclusions: The placentation period is characterized by a weak Ang2 cellular environment in the chorio-villous germinal site in the group of short-term compromised pregnancies, except a highly positive syncytiotrophoblast. The immunoexpression profile in vascular endothelium correlates statistically significantly with placental vascularization index and chorio-villous vascular density in stagnant pregnancies.